Lung sound analysis helps localize airway inflammation in patients with bronchial asthma - Shimoda T; Obase Y; Nagasaka Y; Nakano H; Ishimatsu A; Kishikawa R; Iwanaga T (Journal of Asthma and Allergy, 2017)
Terufumi Shimoda,1 Yasushi Obase,2 Yukio Nagasaka,3 Hiroshi Nakano,1 Akiko Ishimatsu,1 Reiko Kishikawa,1 Tomoaki Iwanaga1 1Clinical Research Center, Fukuoka National Hospital, Fukuoka, 2Second Department of Internal Medicine, School of Medicine, Nagasaki University, Nagasaki, 3Kyoto Respiratory Center, Otowa Hospital, Kyoto, Japan Purpose: Airway inflammation can be detected by lung sound analysis (LSA) at a single point in the posterior lower lung field. We performed LSA at 7 points to examine whether the technique could identify the location of airway inflammation in patients with asthma. Patients and methods: Breath sounds were recorded at 7 points on the body surface of 22 asthmatic subjects. Inspiration sound pressure level (ISPL), expiration sound pressure level (ESPL), and the expiration-to-inspiration sound pressure ratio (E/I) were calculated in 6 frequency bands. The data were analyzed for potential correlation with spirometry, airway hyperresponsiveness (PC20), and fractional exhaled nitric oxide (FeNO). Results: The E/I data in the frequency range of 100–400 Hz (E/I low frequency [LF], E/I mid frequency [MF]) were better correlated with the spirometry, PC20, and FeNO values than were the ISPL or ESPL data. The left anterior chest and left posterior lower recording positions were associated with the best correlations (forced expiratory volume in 1 second/forced vital capacity: r=–0.55 and r=–0.58; logPC20: r=–0.46 and r=–0.45; and FeNO: r=0.42 and r=0.46, respectively). The majority of asthmatic subjects with FeNO ≥70 ppb exhibited high E/I MF levels in all lung fields (excluding the trachea) and V50%pred <80%, suggesting inflammation throughout the airway. Asthmatic subjects with FeNO <70 ppb showed high or low E/I MF levels depending on the recording position, indicating uneven airway inflammation. Conclusion: E/I LF and E/I MF are more useful LSA parameters for evaluating airway inflammation in bronchial asthma; 7-point lung sound recordings could be used to identify sites of local airway inflammation. Keywords: airway obstruction, expiration sound pressure level, inspiration sound pressure level, expiration-to-inspiration sound pressure ratio, 7-point analysis